Membangun Karakter Bangsa Melalui Pembelajaran Sejarah - Titin Ariska Sirnayatin (Universitas Indraprasta PGRI Jakarta, 2017)
The research, titled Building National Character through History Learning, aims to (1) find out the pattern or form of character education development in history learning, (2) know the contribution of history learning to the students’ character development, and (3) identify the obstacles faced by history teachers to developing character through history learning. The methods used in this study are mixed methods with a sequential exploratory approach. The result of the research indicates (1) the ideal pattern or form of character education development according to history teachers is by developing a character-based lesson planning, (2) although still low, history learning has a clear contribution to the development of students’ character, and (3) history teachers face some obstacles to developing the students’ character through history learning, namely the teachers lack skills in designing history Learning Implementation Plan (RPP) containing character education, less optimally use the media or learning resources important to achieve learning objectives containing character education and lack knowledge and skills of developing an alternative assessment in the assessment process.